2021년 봄철 흡습성 에어로졸 입자의 시딩에 의한 인공증우 효과 및 민감도 분석 - 강채연(Chae-Yeon Kang); 송상근(Sang-Keun Song); 문수환(Soo-Hwan Moon); 임윤규(Yun-Kyu Lim); 장기호(Ki-Ho Chang); 채상희(Sanghee Chae) (한국대기환경학회지(국문), 2023)
This study investigated the seeding effect of hygroscopic aerosol particles (CaCl2 and NaCl) on artificial rainfall enhancement (ARE) around the Boryeong Dam (BRD) region located in Chungnam Province in spring (April) 2021. In addition, a sensitivity analysis on the ARE changes caused by the changes in seeding duration and amount of CaCl2 and NaCl was conducted in the study area. This analysis was performed by two sets of simulation experiments: (1) meteorological model simulation with (i.e., SEED) and (2) without a modified Morrison microphysics scheme for CaCl2 and NaCl (i.e., UNSD). The model study indicated the possibility that the seeding of hygroscopic materials around the BRD can affect the ARE in its surrounding/downwind regions. The mean 180 min-accumulated ARE between the SEED and UNSD (SEED-UNSD) due to CaCl2 seeding was 0.44 mm in the study area (15.5% increase relative to 2.84 mm of the UNSD), with the largest ARE of 2.95 mm (35.5% increase relative to 8.32 mm) in regions located northeast of the BRD along southwesterly winds. For NaCl, the mean 180 min-accumulated ARE was 0.47 mm (16.9% increase relative to 2.77 mm), with the largest ARE of 3.93 mm (43.4% increase relative to 9.04 mm) in the same region as CaCl2. The magnitudes of 60 min- and 120 min-accumulated AREs were smaller than those of the 180 min-accumulated ARE. In the sensitivity analysis, the increases in CaCl2 seeding duration (2- and 3-fold) resulted in significant changes (a factor of 3 increase) in the mean 180 min-accumulated ARE in the study area, but there were no distinct changes in case of increased NaCl seeding duration. Unlike the seeding duration, the AREs of both CaCl2 and NaCl were not sensitive to increases in their seeding amount (2- and 3-fold), possibly due to overseeding. KCI Citation Count: 2